Design of Augmented Reality Learning Media for Islamic Religious Education: Encouraging Religious Moderation in Junior High Schools - Ahmad Ta'rifin; Aisyah Zubaidah; Nurlaila Ana; Mohammad Yasin Abidin; Ulul Albab; Hani Hasnah Safitri (STAI Hubbulwathan Duri, 2025)
This study aims to develop an Augmented Reality (AR)–based learning medium for Islamic Religious Education (IRE), integrating the concept of religious moderation in junior high schools. The initiative addresses the need for innovative, technology-driven educational tools that align with current pedagogical trends and religious values. The research employed a Research and Development (RD) approach using the ADDIE model—Analysis, Design, Development, Implementation, and Evaluation. The AR learning media, named DOSIMA, was created as an Android application modeled on a modified Ludo game to deliver educational content through interactive images, videos, and web-based resources. The product was tested in three junior high schools with diverse characteristics: SMP Negeri 2 Kajen, SMP Negeri 1 Petungkriyono, and SMP NU Kesesi. Expert validation was conducted by media, content, and language specialists. Validation results confirmed the feasibility and appropriateness of the media. Field tests indicated a significant improvement in students’ cognitive abilities, with average test scores increasing from 71% to 89.5%. The N-gain score of 63.125% placed the product in the